Menjelajahi Kekayan Cita Rasa Makanan Palestina - Azkiya Lisdiani; Intan Agustin (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This article discusses exploring the rich flavors of Palestinian food in Indonesian learning at Stiepar Yapari Aktripa in Bandung. This study aims to introduce to the people of Bandung, to explore various flavors of food, especially typical of the Middle East. Meanwhile, the problems developed The research instruments are the results of observation, interviews, and researchers as key instruments. The source of this research data is the result of interviews from kitchen restaurant staff, The implementation of sustainable culinary concepts is a challenge because it must balance with Indonesian tastes, including the Bandung area which feels foreign to typical Palestinian food, Palestinian restaurant owners in Bandung aim to improve communication between Indonesia and Palestine through food culture, owners inspired by culinary diversity in Indonesia, especially in the city of Bandung which Many various diverse foods, with that while studying in Bandung the owner thought of opening a Palestinian restaurant to improve communication between Indonesia & Palestine through food culture.